2017
DOI: 10.1590/s1518-8787.2017051006532
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability to the transmission of human visceral leishmaniasis in a Brazilian urban area

Abstract: OBJECTIVE To analyze the determinants for the occurrence of human visceral leishmaniasis linked to the conditions of vulnerability.METHODS This is an ecological study, whose spatial analysis unit was the Territorial Analysis Unit in Araguaína, State of Tocantins, Brazil, from 2007 to 2012. We have carried out an analysis of the sociodemographic and urban infrastructure situation of the municipality. Normalized primary indicators were calculated and used to construct the indicators of vulnerability of the socia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 17 publications
2
12
0
7
Order By: Relevance
“…Geospatial analysis is a statistical approach to analyze data over a geographic region, with applications in environmental science, public health, and other fields. Geospatial statistical techniques, including global and local Moran's indices, can be used to evaluate clustering and dispersion patterns, and have found increasing use in medicine (2325). These techniques have not been applied to the study of DM due in part to the low incidence and prevalence of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Geospatial analysis is a statistical approach to analyze data over a geographic region, with applications in environmental science, public health, and other fields. Geospatial statistical techniques, including global and local Moran's indices, can be used to evaluate clustering and dispersion patterns, and have found increasing use in medicine (2325). These techniques have not been applied to the study of DM due in part to the low incidence and prevalence of disease.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in the North and Northeast states showed a positive correlation between indicators of social and urban structure and the incidence of VL (de Toledo et al ., 2017; Rocha et al ., 2018). Rocha et al .…”
Section: Resultsmentioning
confidence: 99%
“…Toledo et al . 16 studied 1,096 cases of VL reported in Araguaina, a city in Tocantins State, from 2007 to 2012 and observed a large cluster in the central urban area and other smaller clusters in the peripheral areas.…”
Section: Resultsmentioning
confidence: 99%
“…Toledo et al . 16 constructed a vulnerability index based on sociodemographic characteristics of census sectors, but performed the final data analysis at the municipal level since georeferencing of the cases was performed only at the neighborhood level.…”
Section: Resultsmentioning
confidence: 99%